2021
DOI: 10.1111/caim.12471
|View full text |Cite
|
Sign up to set email alerts
|

Practices of creative leadership: A qualitative meta‐analysis in haute cuisine

Abstract: Creative leadership has been studied in different collaborative contexts that can be summarized as facilitating employees' creativity, directing the realization of the creative vision of a leader and integrating different and diverse creative contributions. In this paper, we present the findings from a qualitative meta-analysis of literaturebased accounts of chefs' creative leadership practices from the context of haute cuisine. We bring together both the leader-chefs' and academic authors' understandings of p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 98 publications
0
3
0
Order By: Relevance
“…Emergence is useful for all multi-level phenomena. Often, it functions more as a description than an explanation as it visualizes patterns, structures and properties situated at the macrolevel [81]. Many scholars consider it provisional and quite inadequate and wait for a better theory to come along that would be able to predict, deduce and reduce emergent phenomena to micro-level processes [82].…”
Section: The Construct Of Emergencementioning
confidence: 99%
“…Emergence is useful for all multi-level phenomena. Often, it functions more as a description than an explanation as it visualizes patterns, structures and properties situated at the macrolevel [81]. Many scholars consider it provisional and quite inadequate and wait for a better theory to come along that would be able to predict, deduce and reduce emergent phenomena to micro-level processes [82].…”
Section: The Construct Of Emergencementioning
confidence: 99%
“…Creative thinking improves to work environment and teamwork; creative people and leaders are giving the tone in obtaining creative results (Puccio, Mance & Murdock, 2010). Many specialists in the field found that creative leadership study ease employees' creativity, by developing a creative vision and integrating the diversity of creative contributions (Feuld, Stierand, Dorfler, Boje, Haley, 2021). From a leadership perspective, creative thinking skills are beneficial for a numerous business problems.…”
Section: Creative Thinking In Organizationsmentioning
confidence: 99%
“…As a result of the standardized formal education in the Western world, and the accepted cultural canons in the corporate world, sensing might be perceived as unprofessional and unscientific, making it difficult for managers to admit reliance on it (Sadler-Smith and Shefy, 2004). If they choose to openly tap into sensing at work, without fear of being embarrassed, bringing into alignment social desirability of creative insights and acceptance of sensing, this can lead to increased creativity (Feuls et al, 2021). In working with analytically educated learners, we have brought up various examples from management literature illustrating the value of incorporating sensory-based learning into managerial decision-making, especially under the conditions of uncertainty.…”
Section: What Hinders Openness To Sensory-based Learning?mentioning
confidence: 99%